Review Of Carbon Nanotubes Growth And Synthesis. - Lee, F. Y.; Mohamed, A.R.; Zein, S.H.S.; Chai, S.P. (2004)
Carbon nanotubes are tubular nanostructures derived from rolled graphene planes. Carbon nanotubes are fullerenes related structures but a fullerenes's carbon form a sphere; while a nanotubes are cylindrical. The growth mechanism of carbon nanotubes depend on the synthesis method.